Synthesis and characterization of a potential alginate-gelatin-cholesteryl ester liquid crystals bioink for tissue engineering applications - Abdulmaged Al-Flayyih, Alyaa Idrees (2022)
Tissue engineering (TE) is an innovative approach for tackling many diseases and body parts that need to be replaced by developing artificial tissues and organs. Bioinks play an important role in the success of various TE applications. A bioink refers to a combination of a living cell, biomaterials, and bioactive molecules deposited in a layer-by-layer form to fabricate tissue-like structures. The recent research of bioinks attempts to offer a three-dimensional (3D) complex architecture and control cellular behavior for the printed tissues to improve cells' physical properties and viability. This research attempts to fabricate multi-material bioinks that provide a more physiologically relevant microenvironment to native human tissue and simulate the bioactivity of natural tissues. One of the native extracellular matrix (ECM) important characteristics can be attained by incorporating lipids with the bioinks. The lipid is an essential element for cell membrane and stabilizing bilayer lipid membrane. Subsequently, this research proposes a new multi-material bioink based on alginate (A), gelatin (G), and cholesteryl ester liquid crystals (CELC) biomaterials, namely (AGLC) bioinks. The development of AGLC is carried out by the optimization of different concentrations of A and G gels to obtain a printable formulation of AG gels. Subsequently, the effects of different concentrations of CELC with AG gels are evaluated by using a microextrusion-based 3D bioprinting system to obtain a printed structure with high shape fidelity and minimum width. The AGLC bioinks are formulated using AG gels with 10 % w/v A and 50 % w/v G (AG10-50) and 1 %, 5 %, 10 %, 20 %, and 40 % of CELC. The AGLC bioinks yielded high printability. The printed filament has a minimum width of 1.3 mm at a flow rate of 1 ml/min when the A is 10 % w/v, G is 50 % w/v, and CELC is 40 % v/v (AGLC40). Polymerization of the AGLC bioinks with calcium (Ca²⁺) ions shows well-defined and more stable structures post-printing processes. The physicochemical and viability properties of the AGLC bioinks are examined by FTIR, DSC, contact angle, FESEM, cell cytotoxicity (MTT assay), and cell interaction evaluation methods. In vitro cytotoxicity by MTT assay shows the ability of the bioinks to support the biological activity of HeLa cells. The AGLC bioinks show average cell viability of 82.36 % compared to the control (90 %). Furthermore, cultured cells on the surface of AGLC bioinks show that the bioinks provide favorable interfaces for cell attachment. The overall results show that the AGLC10 and AGLC20 manifest the best promising candidate among the other developed AGLC bioinks.